2013
DOI: 10.1128/jb.00686-13
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome cd1 Nitrite Reductase NirS Is Involved in Anaerobic Magnetite Biomineralization in Magnetospirillum gryphiswaldense and Requires NirN for Proper d1 Heme Assembly

Abstract: bThe alphaproteobacterium Magnetospirillum gryphiswaldense synthesizes magnetosomes, which are membrane-enveloped crystals of magnetite. Here we show that nitrite reduction is involved in redox control during anaerobic biomineralization of the mixed-valence iron oxide magnetite. The cytochrome cd 1 -type nitrite reductase NirS shares conspicuous sequence similarity with NirN, which is also encoded within a larger nir cluster. Deletion of any one of these two nir genes resulted in impaired growth and smaller, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…Deletion of nap genes encoding a periplasmic nitrate reductase not only abolished anaerobic growth and delayed aerobic growth but also severely affected magnetite synthesis and led to the formation of fewer, smaller, and irregular magnetosomes during denitrification and microaerobic oxygen respiration (6). Genetic inactivation of the nitrite reductase NirS resulted in defective growth and biosynthesis of smaller and irregular particles during nitrate reduction (7). In addition to denitrification, which occurs only under suboxic conditions, MSR-1 and related MTB are also capable of aerobic respiration using O 2 as the terminal electron acceptor.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of nap genes encoding a periplasmic nitrate reductase not only abolished anaerobic growth and delayed aerobic growth but also severely affected magnetite synthesis and led to the formation of fewer, smaller, and irregular magnetosomes during denitrification and microaerobic oxygen respiration (6). Genetic inactivation of the nitrite reductase NirS resulted in defective growth and biosynthesis of smaller and irregular particles during nitrate reduction (7). In addition to denitrification, which occurs only under suboxic conditions, MSR-1 and related MTB are also capable of aerobic respiration using O 2 as the terminal electron acceptor.…”
mentioning
confidence: 99%
“…In the alphaproteobacterium Magnetospirillum gryphiswaldense (here referred to as MSR-1) and related MTB, magnetosomes comprise membrane-enveloped magnetite crystals and are aligned in chains (1). Previous studies revealed that magnetosome biosynthesis is largely controlled by a set of about 30 specific genes localized within the genomic magnetosome island (MAI) (2)(3)(4)(5), whereas determinants encoded elsewhere play accessory roles in magnetite biomineralization (6,7). The synthesis of the mixed-valence iron oxide magnetite [FeII(FeIII) 2 O 4 ] was previously proposed to proceed by coprecipitation of balanced amounts of ferrous and ferric iron, which thus requires a precise biological regulation of intracellular redox conditions (8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that study it was also observed by UV-visible absorption spectroscopy of periplasmic protein fractions that the cofactor content of NirS in the P. aeruginosa ⌬nirN strain was different from that in the P. aeruginosa WT strain (15). Later, the same observation was reported for a ⌬nirN strain of Magnetospirillum gryphiswaldense (17).…”
mentioning
confidence: 53%
“…[280] As it was mentioned, MTB exploit the alignment of magnetosomes to migrate into zones where oxygen and other redox active compounds are horizontally stratified. Thus, controlling the level of oxygen to provide microaerobic and anaerobic conditions [281] as well as controlling the redox potential [282] are of two most important factors which are absolutely required for magnetite biomineralization in MTB. Utilizing an oxygen-controlled fermenter provides a precise control over the culture of MTB, especially the most popular investigated model, Magnetospirillium species.…”
Section: Bacteria Mediated Synthesis Of Magnetite Nanoparticlesmentioning
confidence: 99%